UNLOCKING OPPORTUNITIES OF THE ISLAMIC DIGITAL ECONOMY FOR UMMAH SUSTAINABILITY - Nadia Ishak (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2023)
The Islamic Digital Economy (IDE) has emerged as a transformative force, unlocking new opportunities for sustainable development within the global Muslim community (Ummah). This paper explores the multifaceted dimensions of IDE and its potential impact on Ummah sustainability. The IDE encompasses a wide array of digital technologies, including but not limited to fintech, e-commerce, blockchain, and artificial intelligence, all aligned with Islamic principles. By leveraging these technologies, the Ummah can foster economic growth, financial inclusion, and social development while adhering to ethical and Sharia-compliant practices. This paper delves into the key components of IDE, examining its role in promoting entrepreneurship, enhancing financial literacy, and fostering innovation within the Ummah. Moreover, it explores the potential of IDE to address societal challenges such as poverty, unemployment, and income inequality through inclusive and sustainable economic models. In addition, the paper highlights the importance of regulatory frameworks that support the growth of IDE, ensuring that it aligns with Islamic values and principles. It also underscores the need for educational initiatives to enhance digital literacy within the Ummah, empowering individuals to fully participate in the digital economy. Through a comprehensive analysis of the opportunities and challenges associated with IDE, this paper aims to provide insights for policymakers, businesses, and communities seeking to harness the full potential of the Islamic Digital Economy for the sustainable development of the Ummah. By embracing IDE, the Ummah can not only navigate the digital age successfully but also contribute to a more inclusive, ethical, and sustainable global economic landscape.